IMPLEMENTATION OF THE THEMATIC LEARNING FOR CLASS 1B MI ASSA'ADATUDDAAIN 1 IN THE PANDEMIC ERA - Suharsiwi - Suharsiwi; Alif Ainun Firdaus; Agus Suradika (FIP Unimed, 2022)
This study aims to determine the implementation of thematic learning for class 1B MI Assa'adatuddarain 1 in the pandemic era. This research is a qualitative research with case study method with the subject of class 1 B teacher as the research subject. Data collection techniques using interview techniques, observation and documentation. The results of this study concluded that the thematic learning process in this pandemic era went quite well even though there were still obstacles faced. The implementation is carried out in full online and mixed. By implementing 3 components in the form of planning, implementation and evaluation.